Analisis Kepuasan Pengguna SIFITA (Sistem Informasi Fitofarmaka) pada Apoteker dengan Model End User’s Computing Satisfaction (EUCS) di Kota Semarang - Suwarni, Sri; Atmodjo, Timmy Gondho; Setyaningrum, Pertiwi; Farizi, Gilang Rizki Al (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Pharmacists as pharmaceutical personnel who have the authority to be able to practice and provide direct and responsible services to patients. One of the provisions of pharmaceutical supplies is phytopharmaceutical preparations. Phytopharmaceutical preparations have been widely introduced to the community as an alternative therapy, but the problem is that there is still a lack of knowledge about the change from natural medicines to phytopharmaceuticals from Standardized Herbal Medicines or due to a lack of information for explaining the types of phytopharmaceutical preparations. Phytopharmaca Information System or SIFITA is an application designed using web-based software that contains information about phytopharmaca which is expected to help and facilitate pharmacists and the public in obtaining information about phytopharmaca. The purpose of this study was to determine the user satisfaction of SIFITA (Phytopharmaca Information System) with the End User's Computing Satisfaction (EUCS) Model by Pharmacists in Semarang City. Prospective observational method with questionnaire instruments that have been tested for validity and reliability. The population is pharmacists practicing in Semarang City with a sample size calculated using the Slovin Formula with a 90% confidence level of 250 sample responses. Presentation of results is using percentages. The results of the study, namely about the Content side of the use of the SIFITA Phytopharmaca Information System, stated that 76.00% had considered good and 22.00% were very good, the rest were those who said 0.4.00% were not good. Based on the Content variable, it can be seen that respondents' satisfaction is very high regarding the completeness of the application, meeting the needs for services. On the accuracy side, 85.40% said good and 12.60% very good, 0.4.00% not good. The Ease of use side states that 92.00% is good, 8.00% is very good. Form (Format) mentions very good 85.60% good as much as 14.40%.